Guignardia citricarpa resistance to benzimidazoles - Rodrigues, Maria Beatriz Calderan; Andreote, Fernando Dini; Spósito, Marcel Bellato; Aguillar-Vildoso, Carlos Ivan; Araújo, Welington Luiz; Pizzirani-Kleiner, Aline Aparecida (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the resistance of Guignardia citricarpa to pyraclostrobine and carbendazim fungicides, through: growth analysis in culture media amended with the fungicides; leaf decomposition; and production of reproductive structures on leaves naturally infected with these fungi. G. citricarpa was isolated from symptomatic fruits of sweet orange (Citrus sinensis) cultivated in area with intense fungicide application. The sensibility to fungicides of G. citricarpa isolates was evaluated with pyraclostrobine and carbendazim, in the doses 0.5, 1 e 2 mg mL-1 a.i., to verify the effect of selection pressure caused by continuous use of these compounds. Although, reduction on leaf decomposition and on the number of reproductive structures were observed after application of pyraclostrobine and carbendazim, 7.5% of the isolates, evaluated in culture media, exhibited resistance to carbendazim, suggesting that the use of this agrochemical must be combined to other active principles in a consortium to reduce the chances of resistance occurrence. No resistance to pyraclostrobine was observed among tested isolates, what indicates that this could be an alternative compound to be used in combination to carbendazim, to minimize the chance of resistance occurrence.